Posthumanism and the Graphic Novel in Latin America - King, Edward (UCL Press, 2017)
Latin America is experiencing a boom in graphic novels that are highly innovative in their conceptual play and their reworking of the medium. Inventive artwork and sophisticated scripts have combined to satisfy the demand of a growing readership, both at home and abroad. Posthumanism and the Graphic Novel in Latin America, which is the first book-length study of the topic, argues that the graphic novel is emerging in Latin America as a uniquely powerful force to explore the nature of twenty-first century subjectivity. The authors place particular emphasis on the ways in which humans are bound to their non-human environment, and these ideas are productively drawn out in relation to posthuman thought and experience. The book draws together a range of recent graphic novels from Argentina, Brazil, Chile, Mexico and Uruguay, many of which experiment with questions of transmediality, the representation of urban space, modes of perception and cognition, and a new form of ethics for a posthuman world.